ANALISIS PENGARUH KOMORBID (COVID-19 DAN HIPERTENSI) TERHADAP KEMATIAN - Saripah, Saripah; Mirna Aulia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
A viral disease of corona 2019 ( covid-19 ) is severe acute respiratory syndrome corona-2 virus ( sars-cov-2 ) 88 % death caused by sars-cov-1 covid-19 patients.Since indonesia set covid-19 national disaster as the date of 13 april 2020 with the number of cases is increasing.Based on data from 25 march indonesian health ministry by 2020, a total of 192 countries some cases terkonfirmasi 414.179 cases, 18.440 with death cases.Some research shows that the earlier deaths in covid-19 berbedabeda, some state 2,84 %, other research % said 15, and 33 %.Severity covid-19 influenced by endurance, age, and some komorbid disease, some of them are asthma, diabetes militus, and hypertension tujuaan this research to explain how a congenital disease or hypertension that diidap covid-19 by patients into the death of a, and some of the causes of hypertension This research: method uses the study and research of old menggambil literature, and made a reference for this study conclusions: Covid-19 was discovered in Wuhan and spread quickly and dangerously to various countries including Indonesia. Apart from causing high mortality, this virus can also cause other diseases such as hypertension. Risk factors for hypertension include gender and age.